Impact of global uncertainty on the global economy and large developed and developing economies. Issue 22 (8th May 2020) - Kang, Wensheng; Ratti, Ronald A.; Vespignani, Joaquin
ABSTRACT: Global uncertainty shocks are associated with a sharp decline in global inflation, growth and interest rate. Global uncertainty shocks have more protracted, statistically significant and substantial effects on global growth, inflation and interest rate than U.S. uncertainty shocks. When controlling for domestic uncertainty, the decline in output following a rise in global uncertainty is statistically significant in each large country, except for the decline for China. For most economies, a positive shock to global uncertainty has a depressing effect on prices and official interest rates – exceptions are Brazil, Mexico and Russia, which are economies with large capital outflows during financial crises.